Managing the dominant follicle in high-producing dairy cows - Wiltbank, M. C.; Sartori, R.; Vasconcelos, J. L. M. [UNESP]; Nascimento, A. B.; Souza, A. H.; Cunha, A. P.; Gumen, A.; Sangsritavong, S.; Guenther, J. N.; Lopez, H.; Pursley, J. R.; Lucy, M. C.; et al. (Nottingham Univ Press, 2010)
Reduced reproductive efficiency has been reported in high-producing dairy cows. Sources of reproductive inefficiency include decreased expression of estrus, increased diameter of the ovulatory follicle and reduced fertility when cows are inseminated after estrus, increased incidence of double ovulation and twinning, and increased pregnancy loss. To overcome some of these inefficiencies, reproductive management programs have been developed that synchronize ovulation and enable effective timed artificial insemination (AI) of lactating dairy cows. Effective regulation of the corpus luteum (CL), follicles, and hormonal environment are critical for optimizing these programs. Recent programs, such as the 5-day CIDR program, Double-Ovsynch, G-6-G, and estradiol benzoate-CIDR programs were designed to more effectively control one or more physiological events. These events include synchronization of a new follicular wave at the beginning of the program, optimization of the circulating progesterone (P4) concentrations and duration of follicular dominance, optimized reductions in P4 and increases in circulating estradiol (E2) concentrations during the preovulatory period, and tightly synchronized ovulation of a follicle of optimal size and fertility for implementation of timed AI. The success of these programs has been remarkable, although there is substantial variability in effectiveness due to environmental, management, nutritional, genetic, and disease factors as well as potential variability in some aspects of reproductive physiology among commercial dairy farms. Future programs will optimize the reproductive physiology while simplifying the protocol implementation and also match specific reproductive management protocols to specific farms and even specific cows (for example primiparous vs. multiparous).